Endocuff vision-assisted vs. standard polyp resection in the colorectum (the EVASTA study): a prospective randomized study - von Figura, Guido; Hasenöhrl, Moritz; Haller, Bernhard; Poszler, Alexander; Ulrich, Jörg; Brown, Hayley; Abdelhafez, Mohamed; Schmid, Roland M.; von Delius, Stefan; Klare, Peter (Endoscopy, 2020)
Background Cap-assisted colonoscopy is frequently used to facilitate adenoma detection during endoscopy. However, data on how cap assistance influences polyp resection are scarce. We aimed to evaluate the impact of cap assistance with the Endocuff vision device (EVD) on the resection time for colorectal polyps in patients undergoing colonoscopy.Methods A randomized, prospective study was performed in a university hospital in Germany. A total of 250 patients were randomly assigned 1:1 to undergo either colonoscopy with the EVD (EVD arm) or standard colonoscopy without the use of a cap (standard arm). The primary outcome was the average duration of polypectomy. Secondary outcomes included adenoma detection rate, cecal and ileal intubation times, and propofol dosage.Results The use of EVD led to a significant reduction in the median polypectomy time in the EVD vs. standard arm (54 vs. 80 seconds, respectively; P = 0.02). This effect was strongest for polyps ≥ 6 mm. Compared with the standard group, Endocuff assistance also resulted in a shorter cecal intubation time (6 vs. 8 minutes; P = 0.03) and overall colonoscopy time (23 vs. 27 minutes; P = 0.02). In contrast, no difference in withdrawal time was observed. The polyp and adenoma detection rates did not differ significantly between the two groups.Conclusion Endocuff-assisted colonoscopy reduces the duration of polypectomy, which may be due to a more stable scope position during resection. Further studies are needed to investigate whether comparable effects will be seen for other interventions, such as clipping or biopsy sampling.